Między światami. Rzeczywistość w literaturze – literatura w rzeczywistości – rzeczywistość literatury - Ulicka, Danuta (Przestrzenie Teorii, 2018)
The author attempts to reconstruct a short history of modern Polish literary studies not from the perspective of schools or methodological orientations that are usually applied, but from the perspective of what is known in sociology as cultural themes. This point of view offers the opportunity to (re)construct the process of continuity /discontinuity in the whole field of research focused on the problem of reference, which has been recognized as the most important one in Polish studies (as well as in Polish literature, and art) since its beginning in the first decade of the 20th century. In the broader scope the article attempts to rearticulate the definition of the discipline conventionally called “the theory of literature”, and to propose a new way of writing its history.